Smart City: The main assist factor for smart cities Analysis: a systematic review - Triana Puspita Ningrum; Lukito Edi Nugroho; Muhammad Nur Rizal (International Journal of Innovation in Enterprise System, 2021)
Initially, A smart city was originally a solution used to deal with the environmental crisis that tookplace in the 20th century. Smart city concepts derive from the use of technology and knowledge toenhance society's efficiency and competitiveness. The indicators are needed that support theachievement of a smart city. We will analyze the indicators that can impact the smart cityachievement in this article. The aim of this study is to identify the indicators that influence theprocess of developing a smart city in order to be able to help other cities to establish sustainablepolicies and work plans so that they can prepare themselves for a smart city consistently. From theresults of content analysis and descriptions of literature reviews, it is concluded that the indicatorsmost used in the assessment of smart cities are divided into eight groups of indicators, includinggovernance, economy, living, mobility, environment, people, branding, and demography.